Pemahaman Guru PAUD Tentang Pendekatan Saintifik Dalam Pembelajaran Di Wilayah Depok - rohita, rohita (Universitas Hamzanwadi, 2020)
This study aims to determine the early childhood education teacher's understanding of the scientific approach to learning. The sample was 40 early childhood education teachers from 40 institutions in Depok, West Java. The sampling technique uses random sampling. The research method used is quantitative with a survey approach. Data were collected using a questionnaire. Data analysis was performed using descriptive statistical techniques. Understanding indicators include the ability to explain the scientific approach and the ability to describe the scientific approach in learning planning. The results showed that the teacher's understanding of the scientific approach to learning as seen from the ability to explain was 52.5% and the ability to describe 32.5%. The conclusion of this study is the early childhood education teacher's understanding of the scientific approach in learning is in the low category so that the teacher's ability and willingness to continue learning increases knowledge so that the teacher's understanding increases and is able to apply the scientific approach in accordance with the principles of learning based on scientific approaches and principles early childhood learning.